THE IMPLEMENTATION OF RADEC (READ, ANSWER, DISCUSSION, EXPLAIN, CREATING) STRATEGY IN TEACHING ENGLISH VOCABULARY MASTERY AT SD NEGERI PATOMPO II MAKASSAR - Ningsih, Eva Yulia; Sakkir, Geminastiti; Aeni, Nur (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
The objective of this research was to find the effect of the RADEC strategy in teaching English vocabulary  mastery  in  class  VI  SD  Negeri  Patompo  II  Makassar.    This  study  was  a  pre- experimental design with one group given the RADEC strategy. The population of this research were  all  students  of  SD  Negeri  Patompo  II  Makassar.  The  population  of  this  research  used purposive sampling technique. The sample consists of 15 students.  Data were collected using tests (pretest and posttest). The data collection technique used SPSS version 28. The results of descriptive  statistical  analysis  showed  that  the  mean  pretest  result  was  56.13  in  the “poor” classification. The mean posttest result was 85.86 in the “good” classification. Therefore, it can be concluded that the RADEC strategy effect in teaching English vocabulary mastery at SD Negeri Patompo II Makassar. Keywords— RADEC Strategy, Vocabulary Mastery